Money multiplier and business cycle in the United States - Galoci, Peter (2023)
The monetary policy has the power to influence the real economy. Whether it is conducted through discretion or a stable policy rule, it requires some adjustments of the money supply directly connected to the money multiplier. This thesis investigates the relationship between money multiplier and real output in the United States in terms of the direction of causality in order to test the predictions of competing business cycle theories. While monetarism predicts the causality running from money multiplier to real output, both post-Keynesianism and real business cycle theory predict the reverse relationship. The main results of this thesis confirm the monetarist theory for both the period before the financial crisis and the entire time period since 1960. The validity of monetarist prediction, however, depends on the empirical definition of the money supply. While in the shorter of the examined periods, the monetarist prediction holds for the M2 money multiplier, in the longer period, it holds for the money multiplier of M1.